L’université internationale d’été de Santander : la fin d’un projet républicain et le début de l’épuration des personnels universitaires par les insurgés - Élodie Quillier (Les Cahiers de Framespa)
« The International Summer University of Santander: the end of a republican project and the beginning of the purge of the university personnel by the revolted ones. » The Second Spanish Republic creates, by decree of 23/08/1932, the International Summer University of Santander (UIV). The goal is to provide a complementary education given by Spanish and foreign teachers to students of several nationalities, but also to create a space of international exchange for teachers-researchers. We focus first on the study of the syllabuses, of the teachers who got involved in this venture and its international scope. Nevertheless, this republican initiative is quickly going to be annihilated by the pro-Franco coup d'état of July 18, 1936. The university courses in the summer of 1936 are then disturbed by the division between the teachers and students that participated on both sides of the civil war. At the same time, since 1936, the revolted side starts a purge of the university community. By means of the purge files of the university personnel, preserved at the administration general archives (in Alcala de Henares), we study the events that took place during that last summer of the UIV of Santander. We will see how the involvement in the UIV is one of the excuses of the revolted side to accuse the teachers of being « homeland’s enemies », dismiss them from their duties and force them, in many cases, into exile.